2022
DOI: 10.1037/pri0000170
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and mental health care of young adults during COVID-19: A qualitative study.

Abstract: To examine barriers and facilitators to mental health care and use of telemedicine for university students during the COVID-19 pandemic. Key informant interviews of mental health clinicians in 1 university addressed the impact of COVID-19 on students' mental health, adoption of telemedicine, and general mental health care. Theoretical thematic analysis identified positive and negative effects on care. Interviews with 6 psychologists and 4 psychiatrists (50% of invitees; 3 men and 7 women) highlighted social is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Many participants commented on how tiring intensive concentration during teletherapy can be (McBeath et al, 2020); provider interviews with those who treat college students identified the same issues. Online therapy brings the opportunity to treat such young adults remotely, but technical problems and skills, patient distractions, and a lack of confidentiality challenge both patients and therapists (Turner and Siegel, 2022). Another online qualitative survey with 51 mental health care professionals identified three themes of practitioners' experience with online treatment during Covid 19.…”
Section: Current Teletherapy Conditionsmentioning
confidence: 99%
“…Many participants commented on how tiring intensive concentration during teletherapy can be (McBeath et al, 2020); provider interviews with those who treat college students identified the same issues. Online therapy brings the opportunity to treat such young adults remotely, but technical problems and skills, patient distractions, and a lack of confidentiality challenge both patients and therapists (Turner and Siegel, 2022). Another online qualitative survey with 51 mental health care professionals identified three themes of practitioners' experience with online treatment during Covid 19.…”
Section: Current Teletherapy Conditionsmentioning
confidence: 99%
“…Social influence and the stigma associated with mental health care greatly influence this age bracket (18-24 years) and their willingness to answer questions over their mobile devices. Telemedicine offers safety and efficiency, but several limitations prevent wide adoption such as technical problems, patient distraction, lack of confidentiality, compromised therapeutic alliance, and the management of unstable patients through a distance modality [6]. mHealth for an older population has not been entirely successful as well mostly due to the digital divide inherent to older populations and overall digital literacy [14].…”
Section: Rationalementioning
confidence: 99%
“…Depression can be described as a mood (sadness or lack of enjoyment), a symptom, a syndrome, or a disorder [ 5 ]. During the COVID-19 pandemic, college students were particularly affected by depression due to the isolation created by the pandemic thrust upon them during a time in their lives when they expected to be highly socially active [ 6 ]. Anxiety often refers to multiple mental and physiological phenomena, including fear, distress, and a constant state of worry over events or actual situations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%